Media Pembelajaran Kincir Pintar Perkalian Untuk Meningkatkan Kreativitas Anak Dalam Pembelajaran Matematika - Monica Gabriela Nainggolan; Ratih Ayunda; Wahyuni Amanda Hasibuan; Windy Antika (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This journal discusses the smart multiplication learning media to increase children's creativity in learning mathematics. This research aims to create and develop smart wheel learning media for mathematics subjects in elementary school which can be used to support learning so as to help teachers in delivering learning material. The method in this article uses literature study, namely a research method carried out by reviewing literature that is relevant to the research topic. The data collection technique used is a library study technique, where data is collected by reading and analyzing literature that is relevant to the research topic. The results of the research show that the smart multiplication learning media can increase children's creativity in learning mathematics.